Like or dislike: Response of rodents to the odor of plant secondary metabolites - Hansen, Sabine C.; Stolter, Caroline; Imholt, Christian; Jacob, Jens (Integrative Zoology, 2017)
Rodents, including common voles (Microtus arvalis) and house mice (Mus musculus) cause immense pre-harvest and post-harvest losses. Therefore, developing methods that mitigate these losses while maintaining their role in ecosystems is a priority. Several plant secondary metabolites (PSM) which significantly reduce food intake of both species under laboratory conditions have been identified. However, before these can be used in rodent pest management, they must be tested under more natural conditions where other food sources are available. In this study, the odors of 4 PSMs were evaluated for their repellent effects in experiments conducted in semi-natural enclosures. Soil treated with PSMs or untreated soil (experimental control) was placed in an underground box containing food (rolled oats). We quantified the number of visits to each box and could demonstrate that all 4 PSMs reduced the number of visits to treatment boxes in both rodent species. For common voles the combination of methyl nonyl ketone + black pepper oil was the most repellent PSM. House mice made fewer visits to all PSM boxes; boxes with the anthraquinone were visited least. Furthermore, house mice consumed less food from boxes containing soil treated with all 4 PSMs. Our results suggest that PSMs are repellent in murid and microtine rodents under semi-field conditions. In addition, the future use of PSM odors for repelling both pest species, especially house mice, seems promising. Further investigations with other PSMs, different concentrations as well as alternative application methods are needed to repel common voles from attractive crops.